Clean and Productive? Evidence from the German Manufacturing Industry - Ulrich Oberndorfer; Ulf Moslener; Christoph Böhringer; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
We analyze the productivity effects of environmental (green) investment as well as of environmental expenditures and energy expenditures. For this purpose, we follow a production function approach where we account for these investment and expenditure categories as inputs. Based on a panel dataset for the German manufacturing industry between 1996 and 2002 we find that both environmental and energy expenditures do not contribute to production growth. In contrast, environmental investment positively impinges upon production growth as a productivity driver. We thus conclude that environmental regulation should stimulate investment in order to be compatible with economic goals such as productivity.
Keywords: Q58; D24; Q28; 330; environmental performance; environmental regulation; productivity; Industrielle Umweltbelastung; Umweltschutzkosten; Umweltschutzinvestition; Umweltverträgliches Produkt; Umwelttechnik; Innovation; Produktivität; Deutschland